2011
DOI: 10.1001/archgenpsychiatry.2010.200
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Antipsychotic Use in Dementia 1999-2007

Abstract: Use of atypical antipsychotics began to decline significantly in 2003, and the Food and Drug Administration advisory was temporally associated with a significant acceleration in the decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
148
6
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(170 citation statements)
references
References 37 publications
13
148
6
2
Order By: Relevance
“…Even more worrisome, patients treated with dival proex in a substudy were found to experience accelerated brain volume loss and greater cognitive impairment compared with placebo-treated patients [80]. Finally, in a recently published adminis trative health data base study, valproate appeared to have a similar risk of mortality in dementia patients compared with haloperidol, risperi done and olanzapine [81].…”
Section: Rationalementioning
confidence: 96%
“…Even more worrisome, patients treated with dival proex in a substudy were found to experience accelerated brain volume loss and greater cognitive impairment compared with placebo-treated patients [80]. Finally, in a recently published adminis trative health data base study, valproate appeared to have a similar risk of mortality in dementia patients compared with haloperidol, risperi done and olanzapine [81].…”
Section: Rationalementioning
confidence: 96%
“…Conversely AAPs have been found to decrease mortality following long-term cumulative exposure in their original licensed indication schizophrenia [20] (in an adult rather than elderly population). Although the introduction of 'black box warnings' in 2005 led to a decrease in the use of AAPs in dementia, they remain fairly popular agents, prescribed in 9-12% of these patients [21,22].…”
Section: Indications Of Atypical Antipsychotics In the Elderly Editorialmentioning
confidence: 99%
“…An adequate management of BPSD still represents a major challenge since, on the one hand, no treatment is currently approved for this indication and, on the other, several harmful side effects significantly limit the use of available drugs, especially neuroleptics. Conventional and atypical neuroleptics, in fact, are those most commonly used, albeit they are employed off-label [1,2], and several reports and FDA warnings indicate increased mortality and an increased rate of cerebrovascular accidents, besides prolongation of the QT interval with increased risk of torsade de pointes [3]. In order to sort out reliable data on the actual risks for demented patients, some authors have recently introduced the concept of chlorpromazine or haloperidol equivalents (CE and HE, respectively, at 100 mg and 2 mg), allowing a comparison between different drugs and doses [4].…”
Section: Tablementioning
confidence: 99%